2019
DOI: 10.1017/s0967199419000364
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-mediated fast electrical depolarization does not prevent polyspermic fertilization in Paracentrotus lividus eggs

Abstract: SummaryDuring sea urchins fertilization, the activating spermatozoon triggers a series of physiological changes that transforms the quiescent egg into a dynamic zygote. It has been suggested that several of these egg activation events, e.g. sperm-induced plasma membrane depolarization and the Ca2+-linked cortical reaction, play additional roles to prevent the entry of supernumerary spermatozoa. In particular, the abrupt shift in egg membrane potential at fertilization, which is sustained by a Na+ influx, has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
0
14
1
Order By: Relevance
“…This observation does not rule out the possibility that the mechanism fine-tuning the electrophysiological response of the eggs at fertilization is somehow impaired by nicotine in a way that allows multiple sperm entry. However, this model does not provide much explanation for the dose-dependent increase of egg-incorporated sperm, and is not supported by the results of a recent study showing that P. lividus eggs fertilized in the conditions lowering the fertilization potential are mostly monospermic [60,61]. Hence, our observation of dose-dependent effects of nicotine on polyspermy was not convincingly explained by the prevailing models based on the fast electric block and slow mechanical block to polyspermy.…”
Section: Discussioncontrasting
confidence: 91%
“…This observation does not rule out the possibility that the mechanism fine-tuning the electrophysiological response of the eggs at fertilization is somehow impaired by nicotine in a way that allows multiple sperm entry. However, this model does not provide much explanation for the dose-dependent increase of egg-incorporated sperm, and is not supported by the results of a recent study showing that P. lividus eggs fertilized in the conditions lowering the fertilization potential are mostly monospermic [60,61]. Hence, our observation of dose-dependent effects of nicotine on polyspermy was not convincingly explained by the prevailing models based on the fast electric block and slow mechanical block to polyspermy.…”
Section: Discussioncontrasting
confidence: 91%
“…While such rapid polyspermy-preventing mechanism has been suggested to act in diverse organisms [121,122], other authors have ruled out the possibility that the fast electrical block ensures monospermy in sea urchin eggs [123,124]. In line with this, and at variance with the prevailing view that emphasises the depolarization of the egg plasma membrane as the fast mechanism to prevent polyspermy, our laboratory has recently provided evidence that sea urchin eggs remain mostly monospermic, instead of exhibiting the expected polyspermy, when fertilized at conditions that lower the fertilization potential, i.e., artificial seawater with reduced amount of Na + [125][126][127]. As was previously suggested ([5] on page 182), our results have shown that the Fig.…”
Section: Contribution Of Actin Dynamics To Sperm and Egg Activationmentioning
confidence: 60%
“…The characteristic rearrangement of actin fibers in the cortex of monospermic eggs and their concerted translocation towards the center of the zygotes [183] were also inhibited when P. lividus eggs were fertilized in low sodium media. As a result, these monospermic zygotes underwent aberrant cleavages [125]. Seawater salinity changes also alter cortical actin dynamics and the structure of the cytoplasm and organelles , which lead to alteration of the sperm-induced Ca 2+ signals and reduced success rate of development (Limatola N, Chun JT, Santella L. Effects of salinity and pH of seawater on the reproduction of Paracentrotus lividus, submitted).…”
Section: Contribution Of Actin Dynamics To Sperm and Egg Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous archetypes of our understanding regarding the distinct events of egg activation and the events controlling them are continuously being unraveled and questioned, with specifics still being investigated. It is, however, clear that Ca 2+release is an integral component of egg activation in all species studied to date (Cran et al, 1988;Swann and Ozil, 1994;Jones, 1998;Nomikos et al, 2012;Limatola et al, 2019b). Over the last few decades, a number of sperm-derived molecules had been proposed as potential soluble sperm factors responsible for the generation of Ca 2+ oscillations during mammalian fertilization (for more information see Nomikos et al, 2012Nomikos et al, , 2013aNomikos et al, , 2017a.…”
mentioning
confidence: 99%